2000
DOI: 10.1021/ma000485b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Backbone Conformation on the Photoconductivity of Polydiacetylene Chains

Abstract: The thermochromic, solvatochromic, and photoconductive properties of 3-, 4-, 6-, and 9-BCMU (BCMU = poly(butoxycarbonylmethylurethane)-diacetylenes) resulting from changes from rod (red or blue) to coil (yellow) conformations of the polymer backbone have been studied. Photoexcitation of solutions of BCMUs in the rod state results in a large transient photoconductivity as monitored using the time-resolved microwave conductivity (TRMC) technique, while only very small conductivity signals are observed in the coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
(132 reference statements)
0
16
0
Order By: Relevance
“…[122][123][124] Thus, salts of boron compounds are often used in achieving cures of coatings and ink formulations that are based on acrylates and methacrylates. 126,127 Among them, triphenylbutyliborates are preferred, due to their better stability, compared to substituted di-, trialkyl borates. 126,127 Among them, triphenylbutyliborates are preferred, due to their better stability, compared to substituted di-, trialkyl borates.…”
Section: Light-associated Reactions Of Synthetic Polymers 2 Photosenmentioning
confidence: 99%
See 1 more Smart Citation
“…[122][123][124] Thus, salts of boron compounds are often used in achieving cures of coatings and ink formulations that are based on acrylates and methacrylates. 126,127 Among them, triphenylbutyliborates are preferred, due to their better stability, compared to substituted di-, trialkyl borates. 126,127 Among them, triphenylbutyliborates are preferred, due to their better stability, compared to substituted di-, trialkyl borates.…”
Section: Light-associated Reactions Of Synthetic Polymers 2 Photosenmentioning
confidence: 99%
“…Hoofman et al, 127 studied the thermochromic, solvatochromic, and photoconductive properties of 3-, 4-, 6-, and 9-poly[(butoxycarbonylinethyl urethane)-diacetylenes] that result from changes from rod (red or blue) to coil (yellow) conformations of thepolymer backbone. Photoexcitations of the solutions of these polymers in the rod state result in a large transient…”
Section: Photoresponsive Polymersmentioning
confidence: 99%
“…Effective trapping of excitation energy in aggregates observed through photoluminescence experiments indicates that aggregates involving fluorene groups are the most important defects controlling photogeneration in PDV-F. Relatively strong interactions of PDV-F molecules rather closely packed within these aggregates (r 0 = 1.9 nm) should facilitate a formation of long-living interchain excitons that can easily relax non-radiatively via interchain charge transfer (i.e., via the interchain exciton dissociation) [49][50][51]. As a result, a high efficiency of the charge pair formation can be achieved at the high-electric-field limit in this polymer (Fig.…”
Section: Electrical and Photoelectrical Propertiesmentioning
confidence: 99%
“…Matsumoto and co‐workers40 reported that amorphous or partly crystalline PDAs could be isolated as readily soluble polymers when highly crystalline PDAs were dissolved in a polar solvent at a high temperature during refluxing and were then subsequently precipitated. The isolated amorphous or partly crystalline PDAs aggregates exhibited red to yellow chromatic transition by changes in either temperature or solvent quality 40–42. In this work, we prepared polyAzoDA aggregates in 1,2‐dichlorobenzene solution in analogy to the above methods and investigated the effect of the chemical structure variation (including substituent structure of head group and the alkyl side chains length) on the chromatic transitions properties of PDAs aggregates.…”
Section: Introductionmentioning
confidence: 99%